The relationship between procalcitonin, D-dimer, ferritin, troponin and lactate levels with COVID-19 - Ali Gür; Levent Şahin (Acta Medica Alanya)
Aim: Coronavirus disease-2019 patients may experience an increase in inflammation or clotting disorders. It is believed that some biomarkers can be decisive in decision to hospitalize. Our aim in this study was to investigate the relationship between serum procalcitonin, troponin, D-dimer, ferritin and lactate levels, and Coronavirus disease-2019.Methods: Patients suspected of suffering from the Coronavirus disease-2019 and whose serum biochemistry and blood gas tests were performed, were included in the study. The relationships between the blood parameters of the patients with negative or positive Polymerase Chain Reaction test results, and those who were hospitalized or non-hospitalized, were examined.Results: Out of a total of 452 patients, 244 (54%) were male and 208 (46%) were female. There was a statistically significant difference between polymerase chain reaction test positive and test negative groups in terms of procalcitonin, D-dimer, lactate and troponin levels (p˂0.005). There was no statistically significant difference between hospitalized and non hospitalized patient in terms of ferritin (p=0.224). However, there was a significant difference in terms of procalcitonin, D-dimer and troponin levels (p˂0.005).Conclusion: Our results revealed that high serum procalcitonin, D-dimer, lactate and troponin levels are associated with the decision to hospitalize Coronavirus disease- 2019 patients, whereas ferritin levels played no such role.